Computer aided definition of the printing conditions of parts made by FFF - Costa, Sidonie F. (2021)
The growing worldwide use of 3D printing techniques requires the support of scientific research to improve the process and the quality of 3D printed parts. In a previous work, the authors developed a computer code that predicts the temperature evolution and the adhesion at any location of a 3D part produced by Fused Filament Fabrication (FFF). Here, a 3D printed scalpel handle is used as a case study to evaluate the usefulness of the simulation tool in the definition of the printing conditions. Considering a printer with a convection oven, the best built orientation is selected. The results demonstrate the complexity of the heat transfer mechanisms that develop during the deposition stage. For this particular case study, the importance of using a 3D printer fitted with a convection oven is demonstrated, as its positive effect on adhesion cannot be compensated by tuning other process parameters